Tensão na fotografia contemporânea: alguns pontos de vista sobre o mundo - Daniela Goulart Peres (2014)
This research proposes to investigate the socially engaged relationship the photographer has with the world, revealing social injustices, and also as a tool for discover the nuances of the everyday life through traveling. This thesis aims to investigate some aspects of photography from its potential to document the present, despite the recent developments and technical accessibility in the manipulation of digital images. Therefore, Roland Barthes’ view in his book A câmara clara, that photography always carries with it its referente, is the starting point for this analysis. The photographs analysed in this research belong to the fields of fine art photography, journalism and social documentary, fields which have no clearly identifiable boundaries and may even influence each other. The practices of the photographers analysed in this research share the same attitudes in response to phenomenom of the image as a spectacle, offering other possibilities away from the ostensible media flow. Furthermore, they highlight the transcriptional aspect of photography creating photographic series while documentary and subjective. Thus, citing the photographers, their works, and from the idea that the image has a certain contiguity with its external referent, this research establishes a reflection on some aspects of contemporary photography.